The Potential Pharmacological Effects of Natural Product Withaferin A in Cancer: Opportunities and Challenges for Clinical Translation - Devabattula, Geetanjali; Panda, Biswajit; Yadav, Rachana; Godugu, Chandraiah (Planta Medica, 2024)
Cancer is one of the biggest health concerns with a complex pathophysiology. Currently, available chemotherapeutic drugs are showing deleterious side effects, and tumors often show resistance to treatment. Hence, extensive research is required to develop new treatment strategies to fight against cancer. Natural resources from plants are at the forefront of hunting novel drugs to treat various types of cancers. Withaferin A (WA) is a naturally occurring withanolide, a biologically active component obtained from the plant Ashwagandha. Various in vitro and in vivo oncological studies have reported that Withaferin A (WA) has shown protection from cancer. WA shows its activity by inhibiting the growth and proliferation of malignant cells, apoptosis, and inhibiting angiogenesis, metastasis, and cancer stem cells (CSCs). In addition, WA also showed chemo- and radio-sensitizing properties. Besides the beneficiary pharmacological activities of WA, a few aspects like pharmacokinetic properties, safety, and toxicity studies are still lacking, hindering this potent natural product from entering clinical development. In this review, we have summarized the various pharmacological mechanisms shown by WA in in vitro and in vivo cancer studies and the challenges that must be overcome for this potential natural productʼs clinical translation to be effective.
Keywords: Withania somnifera; Solanaceae; Withaferin A; cancer; apoptosis; chemoprevention; metastasis.